Are investments in energy efficiency and renewable energy technologies complementary? An econometric analysis of households’ environmental investments - George Abuchi Agwu (African Journal of Environmental Economics and Management, 2017)
Economic incentives have received much attention in the literature of the two dimensions of environmental friendly energy consumption: energy efficiency and renewable energy investments. This study shows that the incentives, if not well targeted may be irrelevant because household investors in the different dimensions possess different characteristics that policies could target. The findings indicate that investments in renewable energy technologies decrease with age of household investors and not affected by household income constraint while investments in energy efficiency are not affected by age of household investors but by income constraint. Correlation coefficients among all the investment equations in the multivariate model are strongly positive suggesting complementary investment choices across dimensions.